Proud and fearful: Polish mothers’ emotions and motivation to maintain Polish as a HL in transnational exogamous and endogamous families - Joanna Rokita-Jaśkow; Katarzyna Panek (Frontiers in Psychology)
Polish is one of the most common heritage languages (HLs) in various migration contexts, which can be attributed to the motivation and commitment of Polish mothers. However, little is known about the maternal emotions and emotional strain underpinning the motivation to maintain the HL in their children raised abroad. This paper presents the results of a qualitative interview study conducted with 5 Polish mothers from transnational endogamous families and 5 from exogamous families. The qualitative content analysis of the data revealed that mothers in exogamous families experience less pressure to maintain Polish as a HL; nonetheless, in both family types, the mothers are primarily motivated to uphold the HL by feelings of pride in their cultural and linguistic heritage, along with a fear of not being able to transmit the language and identity to their children, thus failing to meet the expectations of extended family members. In endogamous families, mothers are additionally motivated by the prospect of returning and the associated possible future opportunities. The study’s findings indicate that maternal motivations and emotions arise from interactions with extended family members, which may adversely impact their agency in maintaining the HL. It is concluded that greater support for mothers in the bilingual upbringing of their children should be provided by institutions and extended family members.